Interventions for preventing falls and fall‐related fractures in community‐dwelling older adults: A systematic review and network meta‐analysis. Issue 10 (28th July 2021) - Dautzenberg, Lauren; Beglinger, Shanthi; Tsokani, Sofia; Zevgiti, Stella; Raijmann, Renee C. M. A.; Rodondi, Nicolas; Scholten, Rob J. P. M.; Rutjes, Anne W. S.; Di Nisio, Marcello; Emmelot‐Vonk, Marielle; Tricco, Andrea C.; Straus, Sharon E.; et al.
Abstract: Objective: To compare the effectiveness of single, multiple, and multifactorial interventions to prevent falls and fall‐related fractures in community‐dwelling older persons. Methods: MEDLINE, Embase, and Cochrane Central Register of Controlled Trials were systematically searched for randomized controlled trials (RCTs) evaluating the effectiveness of fall prevention interventions in community‐dwelling adults aged ≥65 years, from inception until February 27, 2019. Two large RCTs (published in 2020 after the search closed) were included in post hoc analyses. Pairwise meta‐analysis and network meta‐analysis (NMA) were conducted. Results: NMA including 192 studies revealed that the following single interventions, compared with usual care, were associated with reductions in number of fallers: exercise (risk ratio [RR] 0.83; 95% confidence interval [CI] 0.77–0.89) and quality improvement strategies (e.g., patient education) (RR 0.90; 95% CI 0.83–0.98). Exercise as a single intervention was associated with a reduction in falls rate (RR 0.79; 95% CI 0.73–0.86). Common components of multiple interventions significantly associated with a reduction in number of fallers and falls rate were exercise, assistive technology, environmental assessment and modifications, quality improvement strategies, and basic falls risk assessment (e.g., medication review). Multifactorial interventions were associated with a reduction in falls rate (RR 0.87; 95% CI 0.80–0.95), but not with a reduction in number of fallers (RR 0.95; 95% CI 0.89–1.01). The following single interventions, compared with usual care, were associated with reductions in number of fall‐related fractures: basic falls risk assessment (RR 0.60; 95% CI 0.39–0.94) and exercise (RR 0.62; 95% CI 0.42–0.90). Conclusions: In keeping with Tricco et al. (2017), several single and multiple fall prevention interventions are associated with fewer falls. In addition to Tricco, we observe a benefit at the NMA‐level of some single interventions on preventing fall‐related fractures.